The other side of electronic monitoring: Ethics of care in a control‐oriented technology. Issue 2 (16th April 2018) - Ollivon, Franck
Abstract : This paper aims to question the role of an ethics of care when using a technology of control such as electronic monitoring. Qualitative research based on semi‐structured interviews and ethnographic observation was conducted in two French probation services in order to understand how this alternative to imprisonment is used by State agents. It is argued that, whereas such a technology was designed to ensure an automatic and omniscient control over the probationer, the technical operation of the device leaves room for an interpersonal relationship between the probationer and probation staff. These interactions encourage judges, probation counsellors and surveillance agents to adapt the spatiotemporal frame of the surveillance and therefore make it less difficult to bear.